Effectiveness of soft skills curricular subjects: a case study of two universities, Spain and Mexico - Crespí, Paula; López González, Jorge; Rodríguez-Barroso, Jesús; Virués, Ricardo (Journal of new approaches in educational research, 2025)
Personal competencies are regarded as essential within the framework of lifelong learning, particularly those that are cross-cutting nature in. Currently, few universities include mandatory courses for the development of these competencies. This research presents two cases of universities in Spain and Mexico that have implemented subjects specifically aimed at promoting the development of these competencies. The aim of this study is to assess the effectiveness of the curricular subjects designed ad hoc for the development of intrapersonal and interpersonal competencies of university students. For this purpose, three studies were carried out: two at a Mexican university and one in a Spanish university. The total sample comprised of 1,353 students, with 675 from Spain and 678 from Mexico. The three studies employed a quasi-experimental pretest/post-test design, without a control group, during the 2022–23 academic year. A reliable and valid instrument, the Basic Generic Competencies Questionnaire (BGCQ), was used to assess transversal competencies. The results show that these programs have a significant impact, especially in the development of intrapersonal competencies. This greater impact on intrapersonal competencies may be related to the methodologies used in the programs, especially the individual mentoring sessions.